2014
DOI: 10.1097/iae.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Spontaneous Idiopathic Epiretinal Membrane Separation in Spectral Domain Optical Coherence Tomography

Abstract: Different mechanisms underlying the self-resolution of idiopathic ERM lead to distinct tomographic characteristics and may affect the postseparation visual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 17 publications
0
31
0
5
Order By: Relevance
“…Second, differences in disease chronicity may influence ERM configuration. Previous reports have suggested that ERM formation is a form of wound repair that has an early proliferation phase and a late contraction phase [22,23]. Notably, antidromic configurational changes were not observed from the other types to the GA type.…”
Section: Discussionmentioning
confidence: 70%
“…Second, differences in disease chronicity may influence ERM configuration. Previous reports have suggested that ERM formation is a form of wound repair that has an early proliferation phase and a late contraction phase [22,23]. Notably, antidromic configurational changes were not observed from the other types to the GA type.…”
Section: Discussionmentioning
confidence: 70%
“…14 In our patient, spontaneous ERM peeling was precipitated by a PVD. The incidence of spontaneous ERM peeling is eight times greater in eyes without a preexisting PVD detected by SD-OCT. 14 Combining the insights of expert biomicroscopy, 1,5,7 histopathology/ultrastructural analysis, 12,13 and SD-OCT, 4,6,9,11,14 we propose a series of biomechanical events to explain the evolution and resolution of MPH in our patient (Figure 2). Anteroposterior vitreous traction applied to the foveola ( Figure 2B) resulted in foveal pseudocyst formation ( Figure 2C) and eventual avulsion of the Müller cell cone ( Figure 2D).…”
Section: Discussionmentioning
confidence: 93%
“…Possible mechanisms contributing to spontaneous ERM release in our patient include: 1) attachment of the posterior hyaloid to the ERM with secondary separation of the posterior hyaloid/ERM complex with posterior vitreous detachment (PVD) induction and 2) tangential cell-mediated traction on the inner retinal layer from laser treatment unrelated to PVD induction. In addition, there were some foci of relative space between the inner retina and the ERM (Figure 2A, referred to as "dominant preretinal and intraretinal undulation" by Yang et al 14 ), which may potentially allow for a lower threshold of anterior-posterior force with PVD induction compared with a tightly adherent ERM to the inner retina. It is unclear whether the spontaneous ERM separation in our case is necessarily attributable to the use of FPAL versus conventional laser photocoagulation, nor could we find anything regarding this rare phenomenon in the literature.…”
Section: Discussionmentioning
confidence: 97%